2021
DOI: 10.1177/19476035211053824
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein D as a Potential Biomarker and Construction of a Transcriptional Regulatory-Immune Network Associated with Osteoarthritis by Weighted Gene Coexpression Network Analysis

Abstract: Objective Synovial inflammation influences the progression of osteoarthritis (OA). Herein, we aimed to identify potential biomarkers and analyze transcriptional regulatory-immune mechanism of synovitis in OA using weighted gene coexpression network analysis (WGCNA). Design A data set of OA synovium samples (GSE55235) was analyzed based on WGCNA. The most significant module with OA was identified and function annotation of the module was performed, following which the hub genes of the module were identified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 88 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Currently, with the rapid development of computational algorithms and gene chip technology, many researchers have focused on exploring biomarkers of numerous diseases by application of multiple bioinformatic approaches, which enables in-depth analysis of the whole genome and accelerates the progression of disease study. However, many studies are confronted with limited databases (Gao et al, 2019;Cao et al, 2021;Qin et al, 2021), lack of experimental validation (Gao et al, 2019;Zhang et al, 2020b;Cao et al, 2021), controversial methodology validation (Qin et al, 2021;Li et al, 2022), and unconvincing outcomes. Frontiers in Genetics frontiersin.org chondrocytes (Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, with the rapid development of computational algorithms and gene chip technology, many researchers have focused on exploring biomarkers of numerous diseases by application of multiple bioinformatic approaches, which enables in-depth analysis of the whole genome and accelerates the progression of disease study. However, many studies are confronted with limited databases (Gao et al, 2019;Cao et al, 2021;Qin et al, 2021), lack of experimental validation (Gao et al, 2019;Zhang et al, 2020b;Cao et al, 2021), controversial methodology validation (Qin et al, 2021;Li et al, 2022), and unconvincing outcomes. Frontiers in Genetics frontiersin.org chondrocytes (Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org chondrocytes (Li et al, 2022). Other research groups also only chose one dataset for WGCNA analysis, and many of them lacked validation experiments (Gao et al, 2019;Zhang et al, 2020b;Cao et al, 2021;Wang et al, 2022) or lacked synoviocyte validation data (Qin et al, 2021;Li et al, 2022). None of them verified and evaluated the diagnostic efficacy of candidate markers by mathematical models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we analyzed samples from patients with OA by weighted correlation network analysis (WGCNA) to identify significant modules, along with function annotation of module genes and hub genes. After validation through enzyme‐linked immunosorbent assay (ELISA) and quantitative reverse‐transcription polymerase chain reaction (RT‐qPCR), apolipoprotein D (APOD) was validated as a hub gene coexpressed and downregulated in OA cartilage and synovium 9 . APOD is a secreted glycosylated protein and an atypical lipoprotein, which can bind to several small molecules, such as arachidonic acid, steroids, and cholesterol 10 .…”
Section: Introductionmentioning
confidence: 99%
“…After validation through enzyme-linked immunosorbent assay (ELISA) and quantitative reverse-transcription polymerase chain reaction (RT-qPCR), apolipoprotein D (APOD) was validated as a hub gene coexpressed and downregulated in OA cartilage and synovium. 9 APOD is a secreted glycosylated protein and an atypical lipoprotein, which can bind to several small molecules, such as arachidonic acid, steroids, and cholesterol. 10 Studies have reported the important functions of APOD, such as oxidation resistance, anti-inflammation, and stress resistance.…”
mentioning
confidence: 99%